Reforming Beneficiary Cost Sharing to Improve Medicare Performance - Stephen Zuckerman; Baoping Shang; Timothy Waidmann (SAGE Publishing, 2010)
This paper explores options for reforming Medicare cost sharing in an effort to provide better financial protection for those beneficiaries with the greatest health care needs. Using data from the Health and Retirement Study (HRS) and the Medicare Current Beneficiary Survey (MCBS), we consider how unified annual deductibles, alternative coinsurance rates, and a limit on out-of-pocket spending would alter program spending, beneficiary cost sharing, and premiums for supplemental coverage. We show that adding an out-of-pocket limit and raising deductibles and coinsurance slightly would provide better safeguards to beneficiaries with high costs than the current Medicare benefit structure. Our estimates also suggest that policies protecting these beneficiaries could be structured in a way that would add little to overall program costs.